1961
DOI: 10.1083/jcb.10.2.153
|View full text |Cite
|
Sign up to set email alerts
|

SOME UNUSUAL FEATURES OF FINE STRUCTURE OBSERVED IN HELA CELLS

Abstract: HeLa cells from conventional culture media have been studied in thin sections with the electron microscope; in many cases cells were examined in sets of sections cut in series. The fine structure of the cells is described including three unusual features not hitherto reported. It has been found that numerous cells contained rows of parallel smooth surfaced cisternae spaced about 150 m# apart and communicating with rough surfaced elements of the endoplasrnic reticulum. These cisternae resembled "annulate lamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

1964
1964
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 34 publications
(55 reference statements)
4
32
0
1
Order By: Relevance
“…INTERPHASE: The interphase HeLa cell has often been used in electron microscope studies, and descriptions of it are numerous (18,19). In our studies we have not seen anything not previously noted, and therefore Figs.…”
Section: Resultsmentioning
confidence: 99%
“…INTERPHASE: The interphase HeLa cell has often been used in electron microscope studies, and descriptions of it are numerous (18,19). In our studies we have not seen anything not previously noted, and therefore Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In the same paper he reported that similar lamellar structures were observed also in the hepatocytes of the regenerating rat liver after partial hepatectomy. In the cytoplasm of HeLa cells, EPSTEIN (1961) has observed similar complex membranous structures designating them as "pairs of double cytoplasmic membranes," "closely applied pairs of narrow cisternae" or "paired cisternae." Though he paid no special attention to the relations between these structures and mitosis, it is obvious that he found them in the interphase cells, because of his description that in many cells an area of juxtanuclear cytoplasm was occupied by this structure.…”
Section: Ob Servationsmentioning
confidence: 99%
“…Except those authors to whom the origin and nature of paired cisternae seemed obscure (EPSTEIN, 1961), all discussed these questions rather profoundly. JOHNSON andROBERTS (1964) andLOCKER et al (1968) supposed that paired cisternae may be related to the formation or synthesis of cytoplasmic membranes.…”
Section: Ob Servationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing need to understand the low temperature behavior of Jurkat cells not only for immunological reasons but also for the application in adoptive tumor therapy [46]. And finally, like Jurkat cells, HeLa cells are also an immortal cell line derived from cervical cancer cells [47]. Similar to Jurkat cells, these cells were also chosen for analysis because of their robustness, easy availability, and because they are relatively less understood among the cancer cells.…”
Section: Introductionmentioning
confidence: 99%